2006
DOI: 10.1080/13674580601025165
|View full text |Cite
|
Sign up to set email alerts
|

Context and learning factors in the development of teacher identity: a case study of newly qualified teachers during their induction year

Abstract: This paper reports on a small-scale case study of five newly qualified teachers in one school. The aim of the study was to identify the context and learning factors that enable and constrain the professional growth of new teachers, and to locate the place of formal induction arrangements within the broader experiences of the first year in teaching. The research adopts a narrative-biographical approach, combined with a micro-political perspective, and draws on the findings reported by Michael Eraut concerning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 25 publications
0
18
0
8
Order By: Relevance
“…Reflecting on their experiences, the participants referred to the disparity between theory learned throughout pre-service training and the highly demanding atmosphere of classrooms, and this disparity frustrates teachers as confirmed by earlier studies (Findlay, 2006;Sabar, 2004).…”
Section: Influence Of Environmentmentioning
confidence: 99%
“…Reflecting on their experiences, the participants referred to the disparity between theory learned throughout pre-service training and the highly demanding atmosphere of classrooms, and this disparity frustrates teachers as confirmed by earlier studies (Findlay, 2006;Sabar, 2004).…”
Section: Influence Of Environmentmentioning
confidence: 99%
“…Findlay (2006), reporting findings from a case study of five NQTs completing a school-organised induction programme, noted that respondents reported that they experienced a feeling of isolation within the school, and sometimes within their own subject area. In addition, 'for four of the five respondents a lack of critical feedback and praise was a major complaint, the transition from the semi-protected environment of initial teacher training to beginning teaching [is] difficult because it involves a loss of attention and an expectation that observations of lessons four times a term will suffice' (Findlay, 2006, p. 526).…”
Section: Issues For Newly Qualified Teachersmentioning
confidence: 99%
“…The transition is followed by a process of socialisation within the school during the early years of teaching (Findlay, 2006) and the first full experience of life as a teacher. Capel (1998) reporting findings from a survey of NQTs who had completed a Post Graduate Certificate in Education (PGCE) course, acknowledged that the course could not provide students with experience of all the activities they would face as a qualified teacher.…”
Section: Issues For Newly Qualified Teachersmentioning
confidence: 99%
“…However, this research also suggests that early-career teachers often 'pick and choose' ideal qualities from their teachers in forming expectations of themselves in the role, with Cook noting that a "patchwork of iconic teachers" (p. 280) have a significant impact on how new teachers envisage their own practice. Indeed, many studies address the influence of one's own teachers as a reason for entering the profession (Findlay, 2006;Flores & Day, 2006;Lassila & Uitto, 2016;Macgregor, 2009;Olsen, 2008) demonstrating the impact of this prior observation on an early-career teachers' aspirations.…”
Section: Adjusting Early-career Teacher Expectationsmentioning
confidence: 99%
“…Findlay's (2006) study, for instance, explored the factors which constrain or enable the professional growth in early-career teachers, finding that the main cause of disaffection among teachers was a lack of opportunity to earn praise and initiate meaningful change in their departments -in other words, gain feedback and be recognised. Similarly, McCormack et al (2006) reported that early-career teachers in their study needed confirmation and feedback on their achievements and value in the school, noting the impacts on the confidence and efficacy of the teachers who did not receive this validation.…”
Section: Adjusting Expectations: a Question Of Conditions?mentioning
confidence: 99%